Efficient T Cell Migration and Activation Require L-Plastin - Joshi, Hemant; Morley, Sharon Celeste (Frontiers in Immunology, 2022)
Rapid re-organization of the actin cytoskeleton supports T-cell trafficking towards immune sites and interaction with antigen presenting cells (APCs). F-actin rearrangement enables T-cell trafficking by stabilizing adhesion to vascular endothelial cells and promoting transendothelial migration. T-cell/APC immune synapse (IS) maturation also relies upon f-actin-anchored LFA-1:ICAM-1 ligation. Therefore, efficient T-cell responses require tight regulation of f-actin dynamics. In this review, we summarize how the actin-bundling protein L-plastin (LPL) regulates T-cell activation and migration. LPL enhances f-actin polymerization and also directly binds to the 2 chain of the integrin LFA-1 to support intercellular adhesion and IS formation in human and murine T cells. LPL- deficient T cells migrate slowly in response to chemo-attractants such as CXCL12, CCL19 and poorly polarize towards ICAM-1. Loss of LPL impairs thymic egress and intranodal motility. LPL is also required for T-cell IS maturation with APCs, and therefore for efficient cytokine production and proliferation. LPL-/- mice are less susceptible to T-cell mediated pathologies, such as allograft rejection and experimental autoimmune encephalomyelitis (EAE). LPL activity is regulated by its N-terminal “headpiece” containing serine and threonine phosphorylation and calcium- and calmodulin-binding sites. LPL phosphorylation is required for lamellipodia formation during adhesion and migration, and also for LFA-1 clustering during IS formation. However, the precise molecular interactions by which LPL supports T-cell functional responses remain unclear. Future studies elucidating LPL-mediated regulation of T-cell migration and/or activation may illuminate pathways for therapeutic targeting in T-cell-mediated diseases.